Advanced Machining and Manufacturing Processes - Kumar, Kaushik (Materials Forming, Machining and Tribology,, 2018)
This book covers the various advanced manufacturing processes employed by manufacturing industries to improve their productivity in terms of socio-economic development. The authors present automated conventional and non-conventional machining techniques as well as virtual machining principles and techniques. Material removal by mechanical, chemical, thermal and electrochemical processes are described in detail. A glossary of key concepts is attached at end of the book. .